Intensity of vascular streak dieback in different cocoa clones and various agro-climatic conditions - Indah Anita-Sari; Agung Wahyu Susilo; Niken Puspitasari; Febrilia Nuraini; Bayu Setyawan; Peter McMahon; Philip Keane (Indonesian Coffee and Cocoa Research Institute, 2017)
Vascular streak dieback (VSD) is one of the main diseases on cocoa. This disease can produce a heavy damage in susceptible plants. Agro-climatic condition influences the VSD disease severity level. A study on the relationship between agro-climatic condition and VSD disease severity was conducted in eight locations which were selected based on difference in agro-climatic conditions including altitude, rainfall, number of wet, and dry months. Randomized complete block design was used consisting of eight agro-climatic conditions as treatments which consisted of 200 trees samples, and scored for VSD intensity. A study was also conducted on the response of cocoa clones with different level of resistance at different altitude at Kendeng Lembu, Jatirono, Sungai Lembu, Banjarsari, and Sumber Asin Plantations. A split plot design was applied consisting of two factors. The first factor was location including Pager Gunung (highland) and Besaran (lowland). The second factor was clone resistance with two levels: PA 191 (resistant) and BL 703 (susceptible). VSD scores and stomatal characteristics (stomata number, stomata diameter, and stomata aperture) were determined. The results of experiment showed that VSD scoring differed significantly between the eight agro-climatic conditions. The highest VSD score occurred in the lowland (Gereng Rejo, Banjarsari Plantation, 38 m asl.), where the average annual rainfall was 2161 mm, with five dry months. Cocoa trees in Sumber Asin (580 m asl.), with the average annual rainfall of 2302 mm and 8.5 wet months/3.5 dry months were mostly free of VSD disease. Altitude was positively correlated with rainfall, and negatively correlated with VSD severity. Number of wet months was negatively correlated with VSD severity. Conversely, number of dry months was positively correlated with VSD. The result indicated that genotype, environment, or their interaction did not significantly affect number and aperture of stomata. Although stomatal diameter was significantly affected by environment, genotypes or their interaction with environment did not influence this character.